THE EFFECTIVENESS OF PROGESTERONE HORMONE OR PGF2 AND hCG APPLICATION TO INCREASE REPRODUCTIVE EFFICIENCY OF POSTPARTUM OF ANESTRUS PE GOATS - Syawal, Muhammad; Yusuf, Tuty L; Agil, Muhammad (Universitas Syiah Kuala, 2017)
This study aimed to improve reproductive condition of postpartum anestrus of Etawa crossbreed (PE) goats using PGF2 hormone or progesterone (controlled internal drug release/CIDR-G) and improve pregnancy success from artificial insemination (AI) with human chorionic gonadotrophin (hCG) hormone administration. Administration of progesterone increased estrus by 100%, which was higher than the 70% produced from prostaglandin F2 alfa (PGF2) administration. Estrus onset in CIDR group (35.8013.33 hours) was faster than PGF2 group (45.69.2 hours). Clinical signs of vulva (redness and swollen) were more intense in CIDR-G group (80% and 70%, respectively) compared to PGF2 group (70% and 57%, respectively). Estrus duration in PGF2 group (52.173.34 hours) was longer than CIDR-G group (49.613.56 hours). Pregnancy success in group given hCG was 66.7% while in non-hCG group was 50%. In conclusion, CIDR-G and PGF2 administration is effective to induce estrus of postpartum anestrus PE goats. Administration of hCG at the onset of estrus is effective to improve pregnancy success.